Tunable wavelength-stabilized mode-locked thulium-doped fiber laser beyond 2000 nm - Bartnick, Moritz; Bharathan, Gayathri; Goebel, Thorsten A.; Kraemer, Ria G.; Nolte, Stefan; Bres, Camille-Sophie (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
We demonstrate operation of a tunable mode-locked thulium-doped fiber laser, based on a wavelength-selective chirped fiber Bragg grating (CFBG). By applying strain to the CFBG, we shift its reflection band and can thereby tune the emission-wavelength of the fiber laser between 2022 nm and 2042 nm. We obtain a pulse train at 9.4 MHz repetition rate and a pulse duration between 9.0 and 12.8 ps. To the best of our knowledge, we report the first tunable mode-locked thulium-doped fiber laser using a tunable CFBG as wavelength-selective element.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2 micron; Thulium-doped fiber laser; tunable chirped fiber Bragg grating; tunable mode-locked laser